Software Summaries. - Hendrickson, Harvey S.; Allen, Carl P. (The Accounting Review, 1985)
The article presents information on various software. "Microcomputer Use: Word Processors, Spreadsheets and Data Bases," by Teresa Alberte-Hallam, Stephen F. Hallam and James A. Hallam. This is a well designed, integrated package available for MS-DOS 2.0, Apple and CP/M. The software accompanies the manual, hence, the instructions not hampered by licensing restrictions. The operations and functions are similar to those found with WordStar, SuperCaic and dBase. Each of the application programs is limited: word processing permits seven to ten pages, the spreadsheet is 32 by 64 and the data base will take up to 16 files. The time required to learn to use each of these programs is modest, approximately six hours each; each program can be learned independently. The student manual is well written and easy to follow, taking a hands-on approach. The instructor's manual contains outlines, notes, answers to exercises, and quiz material. The IBM PC Apprentice Series, is a new tutorial workbook, teacher pack, that is a self-teach version. There are approximately 30 titles to date, many of which are recognizable even to those who do not use computers (e.g., dBase II, SuperCaic, Framework, Wordstar, Multimate and Profit Center).